SENSORY VALUE ANALYSIS OF ANCHIO SAUCE (Stolephorus sp.) WITH THE ADDITION OF BROMELIN ENZYME - Nurul Safirahmawadda; Husni Angreni; Tri Widayati Putri; Zul Khairiyah (Journal of Fisheries and Marine Resource Management, 2026)
This study evaluated the effect of bromelain enzyme supplementation on the sensory quality of anchovy (Stolephorus sp.) fish sauce. The experiment was conducted from August to September 2025 using a Completely Randomized Design (CRD) with two treatments: a control without bromelain and a treatment supplemented with 30 g bromelain enzyme. Fresh anchovies were fermented under controlled laboratory conditions using identical salt and water compositions. The resulting fish sauce was evaluated through a hedonic sensory test assessing taste, aroma, texture, and appearance, while amino acid analysis was prepared using High-Performance Liquid Chromatography (HPLC). The sensory evaluation showed that bromelain supplementation slightly reduced panelists' preference for taste (2.9 to 2.7) and aroma (2.8 to 2.7), indicating that enzymatic hydrolysis generated peptides and volatile compounds that moderately altered sensory perception. Conversely, bromelain improved texture, increasing the hedonic score from 3.1 to 3.3, suggesting that protein hydrolysis produced a smoother and more acceptable consistency. Appearance remained unchanged, with both treatments obtaining an average score of 3.7, indicating that bromelain did not affect the visual characteristics of the product. Overall, bromelain enzyme accelerated protein modification while maintaining acceptable sensory quality. These findings suggest that controlled bromelain supplementation has considerable potential as an enzymatic strategy to improve fish sauce processing efficiency while preserving consumer acceptance and supporting the development of higher-quality fermented fish products.